Development of aerobic granular sludge using industrial latex wastewater
An attempt of developing aerobic granules using industrial latex wastewater sludge was conducted. Optimization of cycling time were investigated and assessment of the effect of fluctuating organic loading was performed. Subsequently followed by investigation of physical characteristics of a stable aerobic granules under inconsistent and constant organic loading. Finally, aerobic granular sludge produced was then characterized by a height to diameter ratio (H/D) of 2.7 and 14. Experimental investigation was conducted in sequencing batch reactors R1, R2, R3 and R4 with cycling time of 4 hours after selection of cycling time was conducted based on preliminary investigation. Four batches of experiment were performed to support the objectives of this study. Similar size of sludge flocs was inoculated to all four reactors with reactor configuration of 2.7 and 14 together with various organic loading rate. R1 and R3 was introduced to real latex wastewater with varying chemical oxygen demand (COD) loadings from as low as 0.01 to 0.28 kgCOD/m3/d. However, granules in R1 were cultivated with superficial air velocity (SAV) of 4.25 cm/s, whereas granules R3 utilized SAV of 1.1 cm/s. R2 and R4 was fed with synthetic wastewater with consistent COD loadings of 0.07 kgCOD/m3/d but with different application of SAV. All four reactors achieve granulation, although granules developed in R1 and R3 is bigger and denser than in R2 and R4. But when compared to granules grown in R1 and R3, R2 and R4 granules were less compact and smaller in size. R2 and R4 granules can reach granule size of 0.2 to 0.6 mm within 210 days, compared to R1 and R3 granules that can only developed up to 4.75 mm within 150 days. This result shows significant difference between R1 and R3 with R2 and R4 granules, and that COD loadings appear to be a crucial factor for complete granulation. When R1 granules were compared to granules in R3, an apparent difference of granules characteristics were observed with a high average settling velocity (SV) value in R3 than in R1. On the other hand, R2 and R4, displayed unstable development of granules throughout the study but stable reactor performance after formation of granules. Utilization of a constantly low organic loading rate (OLR) does not seem to favour a stable granules formation, although high height to diameter ratio was applied to enhance the SAV within the reactor in order to intensify shear force optimizing the formation of a more stable and compact granules.